Exploring Forms and Practices of Menstruation in the Changing Social System: A Study of Suryabinayak-05, Katunje, Bhaktapur - Adhikari, Laxmi; Thapa, Mahalaxmi (Baneshwor Campus Journal of Academia, 2024)
Menstruation forms and practices with restriction have a long history not only in a single culture and region but in various religions and cultures may vary according to the level of their cultural norms, values and superstitions. The aim of the study is to explore the forms of practices of menstruation in the changing Nepali society. The qualitative data were collected from the Suryabinayak-05, Katunje, Bhaktapur district. All total 10 potential research participants were selected for in-depth interview along with non-participant observation in the field. The study indicates that the women from Brahmin and Chhetri community affiliated to Hindu religion are practicing almost all forms of discrimination due to menstruation. Stay in a separate room, eating in a separate room, bathing in separate bathroom, be away from social activities and not participate in religious activities. This discrimination should be addressed through awareness programs in the community.